Assessment of Candida auris Response to Antifungal Drugs Using Time–Kill Assays and an Animal Model. (4th October 2017) - Ben-Ami, Ronen; Ashkenazi, Liat; Berman, Judith; Korolker, Nuphar; Novikov, Anna
Abstract: Background: Candida auris is an emerging nosocomial pathogen that is resistant to Fluconazole and variably susceptible to other systemic drug classes. Treatment with echinocandins has been recommended based on MICs in the susceptible range, but supporting in vivo data is lacking. Methods: We tested the MIC of C. auris strains ( n = 12) to fluconazole, voriconazole, posaconazole. anidulafungin, amphotericin B and flucytosine. Representative C. auris strains from Israel and South Africa, and a reference C. albicans strain were analysed using time– kill curve assays. Fungicidal activity was defined as reduction of ≥3 log from baseline CFU/ml. Response to caspofungin treatment was assessed in BALB/c mice immunosuppressed with cyclophosphamide and inoculated with 7 × 10 7 C. auris cells by tail vein injection. Mice were treated from day +1 to day +7 with caspofungin (IP) at doses of 1 or 5 mg/kg and compared with sham-treated controls. Survival was assessed daily. Kaplan-Meier survival analyses were performed and treatment arms were compared using the log-rank test. Results: Drug susceptibility results (MIC50 and MIC90) were: fluconazole, 64 and 128 mg/l; voriconazole, 0.5 and 24 mg/l; posaconazole, 0.5 and 27 mg/l; anidulafungin, 0.03 and 0.06 mg/l; amphotericin B, 2 and 8 mg/l; flucytosine, 0.3 and 1 mg/l. Time– kill curve analyses showed log reduction from baseline CFU concentration of −3.0 to −2.8 for fluconazole (MIC ×1), 5.6– 6.1 for amphotericin B (MIC ×4) and −0.4 to −0.9 for caspofungin (MIC ×16), consistent with fungicidal activity of amphotericin B and weak fungistatic activity of caspofungin. In the mouse model, survival rate was similar with sham treatment (33%) and treatment with caspofungin 1 mg/kg/day (44%) and 5 mg/kg/day (22%), P =  0.7. Conclusion: Despite generally low MIC, caspofungin has only mild fungistatic activity on C. auris and no effect on survival in a mouse infection model. Amphotericin B has fungicidal activity against C. auris . Disclosures: All authors: No reported disclosures.